Prevalence and characteristics of intravertebral enhancement on contrast-enhanced CT scans in cancer patients. Issue 86 (January 2017) - Rasselet, Benjamin; Larbi, Ahmed; Viala, Pierre; Molinari, Nicolas; Tetreau, Raphael; Faruch-Bilfeld, Marie; Taourel, Patrice; Cyteval, Catherine
Highlights: 2.8% of collateral venous circulation seen on CT scan in a cancer population. 37% of intravertebral enhancement in this population with collateral venous circulation. 80.8% of intravertebral enhancements are located between C6 and. 73% of intravertebral enhancements are located ipsilateral to the injection side.  Abstract: Study design: This was a single center, retrospective observational study. Objective: to investigate—in a cancer population—the prevalence and hallmarks of intravertebral enhancement (IVE) detected on contrast-enhanced CT. Summary of background data: Intravertebral enhancements secondary to iodinated contrast stagnation have been described. Cancer patients have an increased risk of perivertebral venous thrombosis or stenosis secondary to several risk factors (cancer or drug induced hypercoagulability, deterioration of venous flow linked to catheter insertion, prolonged immobilization). In case of a high density lesion identified on CT, the diagnostic choice between metastasis and contrast media within bone marrow vessels may be an issue, especially as oncologic follow-up CT scans are usually performed with contrast medium injection. Methods: 2572 contrast-enhanced body CT scans performed in cancer patients over 3 months in the medical imaging department of a university hospital were retrospectively reviewed. IVE was sought when paravertebral venous collateral circulation was detected and bone metastasis ruled out and classified as linear or nodular. Their locations within vertebra, their relation to the injection side and the predominant collateral venous network side were evaluated. Results: Sixty-seven (2.8%) patients had a collateral paravertebral venous system and among them 21 had IVE (37%). There were 208 IVE locations involving 75 vertebrae. 199 IVE were linear-shaped (95.7%) and 9 nodular-shaped (4.3%). 80.8% were located between C6 and T4. 88.9% were localized in the vertebral body. 73.1% were located medially or ipsilateral to the injection side. Conclusion: Intravertebral enhancement is found in 37% of the patients with paraspinal collateral venous circulation when a CT scan is performed for cancer. The ipsilateral or medial position of the IVE relative to the injection side and the side of the dominant perivertebral venous system, and the possibility of connecting the IVE to a paravertebral vein may be in favor of vascular opacification.